THE ROLE OF ORGANIZATIONAL VALUES AND THEIR REFLECTION IN ENHANCING PRODUCT QUALITY, COLLEGE OF TOURISM SCIENCES, AS A MODEL - Abbas Jassim Muhammad; Muhammad Sadiq Muhammad Ali; Ali Latif Odaa (Scholars Digest Publishing, 2024)
The world witnessed rapid developments and environmental changes surrounding the business world during the past century. That emerged as a result of the challenges of the world of information technology, the diversity of products, the increasing customer requirements, and the escalation of competition between business organizations, which made it difficult for the organization to remain as it is without continuing its work and maintaining old and certain procedures or continuing. With different product quality trends, synonymous with and compared to its competitors. This study aims to achieve several goals. That identify prevailing organizational values, and determine the nature of the relationship (interconnected and influential) between the components of organizational values in their dimensions, for example (organizational management, mission management, relationship management, environment management) and their impact on product quality in their dimensions (performance, reliability, Compatibility, responsiveness, special characteristics) for the Holy University of Karbala. The problem of the study is that values constitute a challenge to any organization because of their impact on shaping employees’ behavior, habits, and expectations, which reflects positively or negatively on all the activities of the organization in general. Therefore, the importance of this study stems from the importance of the topic of organizational values and contributing to increasing knowledge accumulation and deepening culture and stereotyping. Organizational behavior and management by values Through the results we obtained from the relationship between organizational values and product quality. In order to achieve the aim of the study, a purposive sample of officials was selected. The decision-makers include (the president of the university and his assistants, deans and assistants, department heads, and rapporteurs) at the Holy University of Karbala. The researcher relied on a questionnaire as a tool to collect the necessary data. (110) questionnaires were distributed. The researcher obtained (104) questionnaires suitable for statistical analysis, with a response rate of (98%) The study included two main hypotheses, from which emerged eight sub-hypotheses that were subjected to statistical analysis. Many statistical methods were used, most notably (the Krolbach alpha scale to measure reliability and validity, the weighted arithmetic mean, the standard deviation, the simple correlation coefficient, the multiple regression coefficient, the... T to indicate the significance of the correlation and influence, the coefficient of determination R2 to indicate the amount of influence), and reached the most prominent conclusions that were inferred in light of the opinions of the study community about its variables. The university being researched showed interest in the dimensions of organizational values. The researcher presented a set of recommendations, the most important of which is that the university administration must invest in the correlation and high influence between Organizational values and product quality help achieve goals efficiently and effectively and achieve a sustainable competitive advantage in the environment of future educational institutions and research.
Keywords: values, organization, organizational values, quality, product